SYNTHESIS OF CARBON QUANTUM DOTS – SILICA (FROM RICE HUSK) DECORATED TITANIUM DIOXIDE AS VISIBLE LIGHT DRIVEN PHOTOCATALYST FOR ACETAMINOPHEN REMOVAL - WONGSO, VIONA (2020)
The presence of pharmaceutical compounds (i.e., acetaminophen) in the aquatic environment has been declared as an environmental issue since researchers found that it has potential risks to human health. Photocatalysis, as a promising method for waste degradation, commonly employs TiO2 as the photocatalyst. However, TiO2 has narrow light absorption and rapid charge recombination rate resulting in ineffective photocatalytic activity. In this project, rice husk-derived carbon quantum dots – silica (CQDs-silica) was decorated on TiO2 matrix through facile mixing approach to minimize the limitations of TiO2.